Stratégies territoriales amérindiennes dans un contexte pluri-ethnique : la région de Auaris (Roraima) - François-Michel Le Tourneau (Confins)
Since 1988, the Brazilian Constitution has been fully applied and vast extensions of territory have been recognized as “Indian lands”. But, even if they are considered by some as protected areas (despite a different legal status), the Indian territories are today facing rapid changes, due to the intensifying contact with other sectors of the Brazilian society. One of the main results of those changes is the diminution of the spatial mobility of indigenous villages, influenced by internal (such as changes in the material culture) as external factors (such as the federal politics or inter-ethnical relationships).In that context, the case of the region of Auaris, inside the Yanomami territory of Brazil, is of particular interest. It gives a complex example of the changes taking place within Indian lands, and of their geographical consequences. Inhabited by near than 2 200 people, Sanuma and Ye’kuana, it has also seen the installation of several “white” infrastructures, thus showing a great diversity of actors. Furthermore, it seems to undergo a social crisis linked with the diminution of the spatial mobility of the villages. In order to analyse the actual deadlock, we remember in this paper this historical constitution of the Auaris region. We then show what are the strategies of the three main social groups present in the area (the Sanuma, the Ye’kuana, the “Whites”). We finally detail what are the current attempts to bypass the actual difficulties, showing that those are often linked with the fact that traditional solutions are difficult to adapt to the current context.